New Textbook in Maritime Fishing Law. K.A.Bekiashev. Maritime Fishing Law: Textbook. – Moscow: TK Velby, the “Prospect” edition, 2007. – 560 p. - E. G. Moiseev (Московский журнал международного права, 2007)
K.A.Bekiashev, an international lawyer who is undoubtedly a leading expert in this sphere, prepared a fifth edition of a textbook in Maritime Fishing Law first published in 1979. The new textbook is necessary for higher and secondary educational institutions students of seagoing disciplines as well as for lawyers and law firms dealing with the problems of Maritime and Fishing Law. 30 years devoted by this prominent scholar to the science of Maritime Fishing Law resulted in the brilliant work under review.The book contains the most up-to-date information regarding the Russian legislation and International Maritime and Fishing Law. The book includes 21 chapter; 152 paragraphs; an appendix with the list of Maritime Fishing Law sources; a bibliography; a subject index.However, the reviewer voices several critical comments. First, the book does not cover the international regime of islands consolidated by the UN Law of the Sea Treaty many of which have an exclusive economic zone of their own. Second, the reviewer wishes the book included a section on the legal regulation of fishing in the Arctic waters. Third, there are problems in the Russian-Norwegian relations connected with fishing in the Spitsbergen archipelago waters. What are the peculiarities of this regime? Are the Norwegian authorities right in their accusations of Russian ships, which allegedly go fishing illegally in that region? Fourth, the book pays little attention to the delimitation of maritime territories, specifically to the delimitation of exclusive economic zones and continental shelves, which often make interstate relations deteriorate. Finally, one should bear in mind that when the book was ready to go to press a new Water Code of the Russian Federation was adopted and a number of changes was introduced to the federal laws on the continental shelf and the exclusive economic zone.